Analisis Kimia Dan Sensoris Marshmallow Air Kelapa Muda dan Gula Kelapa (Cocos Nucifera) - Tineke M. Langi; Novia M.T. Dera; Lucia C. Mandey; Teltje Koapaha; Mukhlis (SINTA Journal (Science, Technology, and Agricultural), 2025)
This study aims to analyze the chemical and sensory characteristics of marshmallows made from young coconut water and coconut sugar, as natural sources of potassium and sodium. The parameters analyzed include potassium content, sodium content, moisture content, pH, and sensory properties. The study employed a Completely Randomized Design (CRD) with four treatments and three replications, varying the concentrations of young coconut water and coconut sugar. The results showed that potassium levels ranged from 3,208–4,345 mg/kg and sodium levels from 482–1,083 mg/kg. The resulting marshmallows had relatively high moisture content (28.15–39.38%) and low pH (5.03–5.93). Sensory evaluation indicated good acceptance by panelists, characterized by a chewy texture, distinctive coconut sugar aroma, and natural brown color.